Arabian romantic : poems on bedouin life and love - Ibn Subayyil, ʻAbd Allāh, approximately 1853-1933 (New York University Press, 2018)
Love poems from late nineteenth-century Arabia Arabian Romantic captures what it was like to live in central Arabia before the imposition of austere norms by the Wahhabi authorities in the early twentieth century: tales of robbery and hot pursuit; perilous desert crossings; scenes of exhaustion and chaos when water is raised from deep wells under harsh conditions; the distress of wounded and worn-out animals on the brink of perdition; once proud warriors who are at the mercy of their enemy on the field of battle. Such images lend poignancy to the suffering of the poet's love-stricken heart, while also painting a vivid portrait of typical Bedouin life. Ibn Sbayyil (ca. 1853-1933), a town dweller from the Najd region of the Arabian Peninsula, was a key figure in the Nabati poetic tradition. His poetry, which is still recited today, broke with the artifice of the preceding generation by combining inherited idiom and original touches reflecting his environment. Translated into English for the first time by Marcel Kurpershoek, Arabian Romantic will delight readers with a poetry that is direct, fluent, and expressive, and that has entertained Arabic speakers for over a century.